Biomimicked high-aspect-ratio hierarchical superhydrophobic polymer surfaces. Issue 1 (March 2014) - Mattaparthi, Srinadh; Sharma, Chandra S.
Abstract : There is an abundance of plant surfaces in nature, which inspires scientific community to replicate and prepare artificial superhydrophobic surfaces. However, most of these studies are limited to low-aspect-ratio structures as found in petals and leaves. In this study, the authors chose Canna indica, a garden plant belonging to Cannaceae family, as a model plant. The C. indica seedpods possess high-aspect-ratio multiscale structures and also show superhydrophobic behavior. These high-aspect-ratio hierarchical structures as found in C. Indica seedpod were then successfully replicated by replica molding in different polymers such as poly(dimethylsiloxane) (PDMS) and resorcinol–formaldehyde (RF)-based xerogel. These biomimicked polymer surfaces exhibit superhydrophobicity as confirmed by water contact angle measurement. The original seedpod shows water contact angle of 151°, while negative PDMS and RF gel replica with high-aspect-ratio structural patterns show water contact angle of 146 and 155°, respectively. Thus, the biomimetic approach depicted here not only allows the facile fabrication of high-aspect-ratio structures over a large area but also provides a low-cost alternative to produce superhydrophobic polymer surfaces.